Análise bioquímica e equilíbrio ácido-base em Biomphalaria glabrata (Say, 1818), hospedeiro intermediário do Schistosoma mansoni (Sambon, 1907), sob a exposição ao Stryphnodendron polyphyllum (Martius, 1837), planta moluscicida do Cerrado brasileiro. - FERREIRA, Cirlane Silva (2006)
The state of Goiás represents a high risk to schistosomiasis stablishment area The presence of the intermediate host Biomphalaria sp added to high migration levels of people from endemic regions of the country are evidences that favour the installation of this disease life cycle In this state of Goiás there are reports of high parasitary intensity and even cases of paraplegia associated with schistosomiasis. The Stryphnodendron polyphyllum (Martius 1837) known locally as Barbatimão de folha pequena is reported as a molluscicide plant This paper assesses the activity of gross bark extracts from S polyphyllum on the metabolism and on the acid-alkaline balance of B glabrata The mollusks were exposed to the extract at 25 and 50 mg/L concentrations for 24 hours and compared to a control group The concentrations of glucose calcium urea proteins and the activity of the following enzymes dehydrogenases lactate and aminotransferases were estimated using the spectrophotometry method The organic acids citrate propionate α- cetoglutarate succinate acetate malate fumarate pyruvate and lactate were detected and quantified using the liquid chromatography method Of all the organic acids found in the hemolymph, only citrate and propionate presented a significant alteration The acid-alkaline balance was verified by measuring the concentrations found in the pH oxygen carbonic gas carbonate ions and oxygen saturation using Radiomiter equipment The S polyphyllum extract tested proved effective due to celular toxicity on B glabrata(Say 1818) Alterations verified in the biochemical dosages reflect the metabolic disturbances in the hemolymph of the mollusk The Cirlane Silva Ferreira x extract interference caused an increase in the levels of glucose urea calcium aspartate alanine aminotransferases and carbonic gas pressure simultaneously causing a decrease in the levels of lactate dehydrogenase pH oxygen pressure carbonate ions and oxygen saturation This study confirms the bioactivity of the S polyphyllum aqueous extract on B glabrata One of the main contributions of the methodology used is that it enabled observation after direct contact with the extract that proved bioactivity on the metabolism of the mollusk The analysis of the aqueous extract taken from the bark of the barbatimão may be the basis for new and less toxic as well as less costly alternative for the control of schistosomiasis in Brazil, where the savannah is vast and financial resources are often scarce in the health sector